Power Struggle: Chileans Face Off on Hydroelectric Dams. - Witte, Benjamin (NACLA Report on the Americas)
Developed as a joint venture by Spanish electricity giant Endesa and Chilean entity Colbún, the Aysén Project is a $2.5-billion plan to construct hydroelectric dams in Chile's Region XI, an isolated and sparsely populated zone also known as Aysén. The project entails damming both of Aysén's two largest rivers, the Baker and the Pascua, to help meet Chile's growing demand for electricity. However, the venture has attracted considerable opposition, with critics lambasting it on environmental grounds and pointing to the all too often ignored alternative of conservation. In additions, opponents of the project criticize Chile's energy policy for reinforcing the country's age-old development model based on the export of raw materials.